Pemberdayaan Siswa-Siswi SMA Negeri 3 Kota Sibolga tentang Pelatihan Sederhana Bantuan Hidup Dasar (BHD) dalam Upaya Memberikan Pertolongan Pertama - Ramlan Ramlan; Esrina Esrina; Muthoh Hariani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Community service by the D-III Nursing Study Program in Central Tapanuli, Medan Ministry of Health Polytechnic, was carried out in the form of material presentations and demonstrations to students of SMA Negeri 3 Sibolga about Basic Life Support as first aid. Basic Life Support (BHD) is a series of first aid that is carried out to help anyone who experiences respiratory or cardiac arrest. One solution for first aid is to educate the public about Basic Life Support so that the possibility of brain cell damage will be smaller and give the victim enough time to be taken to the hospital on time. The target of service activities is 100 students of SMA Negeri 3 Sibolga. The aim of this Community Service is to realize community service as one of the Tri Darma activities of Higher Education, increasing the knowledge and skills of students in providing basic life support as emergency first aid. The methods used are counseling, training and question and answer/discussion and evaluation. After the counseling and demonstration of Basic Life Support was carried out, the results showed that the majority of respondents had sufficient knowledge at 58%, 35% had good knowledge and 7% had less knowledge. Competency evaluation is carried out by giving participants the opportunity to demonstrate directly the implementation of BHD using a phantom. The results obtained were that 63% had capable category skills and 37% had less capable skills, meaning that students still received assistance.